State production of cultural nationalism: political leaders and preservation policies for historic buildings in France and Italy. Issue 1 (28th December 2017) - Thatcher, Mark
Abstract: Although cultural and political nationalism have often been treated as separate, recent studies argue that they are linked because the state produces policies such as promotion of cultural heritage to further nation building. The article examines the conditions that favour national political leaders adopting policies to protect historic buildings for aims of political nationalism. It compares France and Italy, focusing on the period after 1870. It finds that in both countries, national political leaders have introduced extensive protection of historic buildings when faced with major challenges such as war, regime change or pressures from localism or supporters of cultural nationalism as part of wider strategies to build and reinforce the nation state. But Italy extended protection earlier and more deeply than France, suggesting in a later nation state with strong inherited cultural nationalism but major political weaknesses and, national political leaders may introduce earlier, more far‐reaching and more layered legal protection than in states created earlier and with fewer weaknesses.